To solve the equation \(-4(3x + 10) - 2 = 54\), follow these steps:
-
Distribute \(-4\) to both terms inside the parentheses: \[ -4 \cdot 3x - 4 \cdot 10 - 2 = 54 \] This simplifies to: \[ -12x - 40 - 2 = 54 \]
-
Combine the constants on the left side: \[ -12x - 42 = 54 \]
-
Add \(42\) to both sides of the equation to isolate the term with \(x\): \[ -12x = 54 + 42 \] \[ -12x = 96 \]
-
Now, divide both sides by \(-12\): \[ x = \frac{96}{-12} \] \[ x = -8 \]
So the solution is: \[ x = -8 \]
The correct response is \(x = -8\) (or "x equals negative 8").